Hospital admissions for non-fatal drowning in Finland, 2002–2023: a nationwide population-based register study - Philippe Lunetta; Kari Haikonen (Injury Epidemiology)
Abstract Background Nationwide epidemiological data on non-fatal drowning are lacking. The purpose of this study was to provide and analyze data on incidence and time-trends of hospital inpatient admissions for drowning in Finland. Materials and methods The Finnish Hospital Discharge Register was retrospectively searched for all inpatient hospitalizations due to unintentional and intentional drowning from January 1, 2002 to December 31, 2023 and included the entire Finnish resident population. The main outcome measure was the annual number of and crude incidence rates (n/100 000 population) of hospital admissions for drowning. The Poisson regression method was used to analyze time-trends. Results A total of 1205 patients (mean 54.8 per year, CI95: 47.4–62.2; 52.7–68.9; mean age: 40.8 years, CI95: 39.2–42.3; male to female RR: 2.6) were hospitalized for drowning (1079 unintentional, 64 self-harm, 7 assault, 55 undetermined). The mean crude incidence rate of hospital admissions for drowning was 1.01 /100 000/year and decreased from 1.73 in 2002 to 0.52/ 100 000 persons in 2023. The incidence of such non-fatal drownings (0.91/100 000/year) significantly decreased during the study period (-4.9% / year; p < 0.0001). The age distribution showed two peaks with a first peak in children 0 to 4 years old and a second one among individuals 45 to 64 years old. The most frequent setting was a natural body of water, followed, in adults, by ice-covered bodies of water and leisure boating and, in children, by swimming pool/ bathtub. The rate ratio between non-fatal accidental drowning requiring hospitalization, and fatal drowning was exceedingly low (0.3). Conclusions Non-fatal drownings are crucial for assessing the overall burden of drowning although, in Finland, hospital admissions for drowning have significantly declined, and fatal drownings outnumber non-fatal drownings, at least those requiring inpatient hospital care. The epidemiological profile of non-fatal drowning may substantially vary, even among high-income countries.